2017
DOI: 10.1152/ajprenal.00092.2017
|View full text |Cite
|
Sign up to set email alerts
|

Architecture of the rat nephron-arterial network: analysis with micro-computed tomography

Abstract: Among solid organs, the kidney's vascular network stands out, because each nephron has two distinct capillary structures in series and because tubuloglomerular feedback, one of the mechanisms responsible for blood flow autoregulation, is specific to renal tubules. Tubuloglomerular feedback and the myogenic mechanism, acting jointly, autoregulate single-nephron blood flow. Each generates a self-sustained periodic oscillation and an oscillating electrical signal that propagates upstream along arterioles. Similar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(32 citation statements)
references
References 45 publications
2
30
0
Order By: Relevance
“…It, however, does not mean that the observed clusters were limited to, at the most, 40 nephrons. When considering renal vascular topology, it is to be expected that within the 1.5x1.5µm field of view, we observe arterioles that arise from different non-terminal arteries 33 . Depending on the branching order, each of such arteries can branch into ten-several hundreds of nephrons, but only a small number of these nephrons will have arterioles reaching close enough to the surface to be segmented from LSCI images.…”
Section: Discussionmentioning
confidence: 93%
“…It, however, does not mean that the observed clusters were limited to, at the most, 40 nephrons. When considering renal vascular topology, it is to be expected that within the 1.5x1.5µm field of view, we observe arterioles that arise from different non-terminal arteries 33 . Depending on the branching order, each of such arteries can branch into ten-several hundreds of nephrons, but only a small number of these nephrons will have arterioles reaching close enough to the surface to be segmented from LSCI images.…”
Section: Discussionmentioning
confidence: 93%
“…The cortical tissue was pressed through a 180-m sieve and incubated in a digestion solution (0.016% collagenase D, 0.016% trypsin inhibitor, 0.016% dithiothreitol, and 0.016% albumin) at 36.5°C for 35-45 min. The preglomerular microvessels, consisting of interlobular arteries [also defined as cortical radial arteries (26)] and afferent arterioles, were carefully separated from tubular tissue under a stereomicroscope and transferred to a digestion solution containing 0.05% dithiothreitol, 0.14% papain, and 4% albumin dissolved in a low-Ca 2ϩ (50 M) PSS at 36.5°C. After a 15-to 25-min incubation period, the mixture was centrifuged (900 g for 2-3 min) to pellet the dispersed cells.…”
Section: Isolation Of Pmvsmcs For [Ca 2ϩmentioning
confidence: 99%
“…Sled et al observed a high degree of similarity in the distribution of vessel diameters within mouse kidneys based on micro-CT images (31). Marsh et al scanned polymer cast of a rat renal vasculature using low-and high-resolution micro-CT imaging (23). They measured the segmental lengths of arteries and afferent arterioles and distances between arteriolar pairs to study vascular organizational patterns in the arterial-nephron network.…”
Section: Introductionmentioning
confidence: 99%